The Relationship Between the Oil Content with the Abundance of Diatoms in the Waters of Kuala Tanjung Batubara Districs North Sumatera. - Jonter Sitepu; Yusni Ikhwan; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
A study of the relationship between oil content and the abundance of diatoms was conducted in September 2016 in the waters of Kuala Tanjung Batubara District of North Sumatra Province. Seawater samples (for oil analysis and diatoms) were collected from 4 stations. Analysis of oil content and identification of diatom was done conducted in laboratory of Chemistry and Laboratory of Marine Biology, Faculty of Fisheries and Marine Science, University of Riau. The results show that all water quality parameters measured in this study are within the tolerance range for survival of marine organisms. The oil content ranges from 0.1560 to 0.2871 ppm and diatom abundance ranges from 55 to 134 ind / l with 10 species. Based on the results of simple linear regression test, the relationship between oil content with diatomic abundance has a very strong relationship with mathematical equations y = 236,3 - 647,8x with coefficient of determination (R2) = 0,762 and correlation coefficient r = 0,873. The value of r represents a strong relationship with a negative value meaning that with increasing oil content in the waters, the abundance of diatoms in the waters will decrease.Keywords: relationship, oil content, abundance, diatoms, Kuala Tanjung.